A novel metal–organic framework (MOF)–mediated interfacial polymerization for direct deposition of polyamide layer on ceramic substrates for nanofiltration - Bao, Yueping (2020)
A facile metal–organic framework (MOF)‐mediated interfacial polymerization (IP) method is developed to prepare a polyamide (PA) layer directly on the ceramic substrate for nanofiltration. MOF is introduced to connect ceramic substrate and PA layer via chemical bonding, resulting in a robust separation layer. The optimization of IP can be controlled by MOF growth process via tuning the surface roughness as well as hydrophilicity. This method will provide a new way for the preparation of next generation of organic–inorganic composite membranes.